Broadcasting Protocol for Effective Data Dissemination in Vehicular Ad Hoc Networks - Sanmugaraja, Lakshmanaprakash (Curtin University, 2018)
VANET topology is very dynamic due to frequent movements of the nodes. Using beacon information connected dominated set are formed and nodes further enhanced with neighbor elimination scheme. With acknowledgement the inter section issues are solve. A modified Broadcast Conquest and Delay De-synchronization mechanism address the broadcasting storm issues. Although data dissemination is possible in all direction, the performance of data dissemination in the opposite direction is investigated and compared against the existing protocols.